Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

solve the equation in factoral form

 

(x+3)(x-2/5=0



Sagot :

Lilith
[tex](x+3)(x-\frac{2 }{5})=0 \\ \\x+3 =0 \ \ \vee \ \ x-\frac{2}{5}=0\\ \\x = -3 \ \ \vee \ \ x=\frac{2}{5}[/tex]